EP436 The kinetic profile and clinical implication of SCC-ag in squamous cervical cancer patients undergoing radical hysterectomy using simoa assay: a prospective observational study. (1st November 2019) - Ye, S; Sun, X; Kang, B; Wu, F; Zheng, Z; Xiang, L; Liang, J; Yang, H
Abstract : Introduction/Background: To study the kinetic profile and clinicopathological implication of squamous cell carcinoma antigen (SCC-Ag) in cervical cancer patients who underwent radical hysterectomy by a self-developed Single Molecule Assay (Simoa) immunoassay. Methodology: We prospectively enrolled cervical cancer patients who were scheduled for surgery between 2016/04 and 2017/06. Consecutive serum samples were collected at five points: Day 0 (the day before surgery), Day 4 (post-operative day 4), Week 2–4, Month 2–4 and Month 5–7. A total of 92 patients and 352 samples were tested using Simoa, which were compared with commercially available Architect assay. The median SCC-Ag values for each time-point and kinetic profiles were analyzed. We further assessed the correlations between SCC-Ag value/profiles and clinicopathological parameters. Results: We demonstrated that Simoa was quite comparable to Architect. The median SCC-Ag value for each time-point using Simoa was 2.49ng/mL, 0.66ng/mL, 0.61ng/mL, 0.72ng/mL, 0.71ng/mL, respectively. The kinetic curve showed that the SCC-Ag levels decreased dramatically after surgery, and then stabilized and fluctuated to some extent within 6 months. Patients with some intermediate- or high-risk factors had significantly higher SCC-Ag values than those negative counterparts before surgery and within 3 months after surgery, but reach the same levels after 6 months. Furthermore, although patients with positive lymph node had sustained higher SCC-Ag values compared to those negative counterparts, similar kinetic tendencies were observed in both groups. Different from this finding, in comparison to the patients with surgery only, patients who received post-operative adjuvant treatment had significantly higher SCC-Ag values at the beginning, while no difference existed after completion of treatment. Conclusion: The user-friendly Simoa SCC-Ag assay was established for clinical setting. The SCC-Ag levels were higher in intermediate- or high-risk patients, whereas, the kinetic trend of SCC-Ag might be mainly affected by postoperative adjuvant therapy. The prognostic role needs follow-up data, which warranted further investigation. Disclosure: Nothing to disclose.